Answered

Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

using the system of substitution
2x-3y=12
x + y=9


Sagot :

Here! I hope this helps! :) Work is in the picture
x=7.8
y=1.2
(7.8,1.2)
View image BashfulTrombone
iGreen
2x - 3y = 12
x + y = 9

x + y = 9

Subtract 'x' to both sides:

y = -x + 9

Plug in -x + 9 for 'y' in the first equation

2x - 3(-x + 9) = 12

Distribute -3:

2x + 3x - 27 = 12

Combine like terms:

5x - 27 = 12

Add 27 to both sides:

5x = 39

Divide 5 to both sides:

x = 7.8

Plug this into any of the two equations to find 'y':

x + y = 9

7.8 + y = 9

Subtract 7.8 to both sides:

y = 1.2

So the solution is (7.8, 1.2).
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.